Concurrent optimization of customer requirements and the design of a new product - Piedras, Hugo; Yacout, Soumaya; Savard, Gilles (International journal of production research, 2006)
This paper proposes a mathematical programming technique to optimize the product development process. Using a concurrent engineering approach, the paper presents a formulation that maps the different stages of product development. The decision variables of these stages are then determined simultaneously. While the Quality Function Deployment Technique (QFD) is based on a qualitative sequential approach, this paper proposes a holistic quantitative approach to concurrent product-process optimization. The mathematical programming technique is applied to the first two stages of product development: the optimization of customer satisfaction and the product's design.